(untitled) (International Journal of Engineering and Computer Science, 2025)
The accelerating complexity of today’s digital products demands that software-engineering processes—not merely management models—evolve in lock-step with change. This study examines how traditional, Agile and hybrid software-development life-cycles affect technical success metrics. Focusing on engineering practices such as continuous integration, automated testing, incremental refactoring and time-boxed iterations, we apply a mixed-methods design that combines factor and correlation analysis, structural-equation modelling (SEM) and semi-structured interviews with practicing developers. The findings reveal a strong positive association (r ≈ +0.7) between systematic use of Agile practices and improvements in defect density, mean time to restore, deployment frequency and stakeholder satisfaction, while simultaneously lowering intra-team stress. Organisational culture and Agile maturity significantly moderate these effects. The paper distils practical recommendations for developers, team leads and technical executives seeking to enhance code quality and delivery resilience in volatile environments.